When the company does not matter: High‐quality ant seed‐disperser does not drive the spatial distribution of large‐seeded myrmecochorous plants. (23rd December 2019) - Leal, Laura C.; Silva, Daniel Paiva; Peixoto, Paulo E.C.
Abstract: Mutualisms are one of the main forces shaping species spatial patterns at all geographic scales. In generalised mutualisms, however, the dependence among partners is highly variable in time and space, and therefore, the effect of diffuse mutualisms on species geographic distributions is unclear. Myrmecochorous seeds in Brazilian semi‐arid vegetation are dispersed by several ant species. However, large‐seeded species are especially dependent on dispersal by the giant ant Dinoponera quadriceps, which is the main disperser of such diaspores and the species that provide the longest dispersal distance among ant species in this system. Hence, we hypothesise that the presence of D. quadriceps shapes the distribution of large‐seeded, but not the distribution of small‐seeded myrmecochorous plant species. To evaluate this hypothesis, we modelled the potential distribution of two large‐seeded (which are predominantly dispersed by D. quadriceps ) and two small‐seeded (which are barely dispersed by D. quadriceps ) Euphorbiaceae species and the potential distribution of D. quadriceps . We analysed the relationship between the occurrence suitability of D. quadriceps and the occurrence suitability of plant species. We found that the potential distribution of both large‐seeded and small‐seeded myrmecochorous plants was unrelated to D. quadriceps occurrence suitability. It means that the disproportional benefits provided by high‐quality disperser at local scales may not emerge at broader geographical scales. In Caatinga vegetation, diaspores are submitted to strong abiotic filters that constraint seed germination and establishment after the dispersal phase. Such abiotic filters may dilute the initial benefit provided by long‐distance dispersers. Therefore, we suggest that in dry environments like the Caatinga, the benefits of long‐distance removals should be outweighed by the risk of reach new habitats with unfavourable conditions for germination and establishment.